(untitled) - Moriarty, Sandra E. (Boston, 2015)
This text tracks the changes in today's dynamic world of media and marketing communication as well as the implications of these changes to traditional practice and presents them to students through an accessible, well-written approach. This edition highlights the increasing importance of consumers as the driving force in today's advertising strategies, social media, and the Internet evolution/​revolution. It also includes an increased IMC (integrated marketing communication) and brand focus.
Keywords: Quảng cáo,Advertising